Plasma protein changes reflect colorectal cancer development and associated inflammation - Urbiola-Salvador, Víctor; Jabłońska, Agnieszka; Miroszewska, Dominika; Huang, Qianru; Duzowska, Katarzyna; Drężek-Chyła, Kinga; Zdrenka, Marek; Śrutek, Ewa; Szylberg, Łukasz; Jankowski, Michał; Bała, Dariusz; Zegarski, Wojciech; et al. (Frontiers in Oncology, 2023)
Introduction Colorectal cancer (CRC) is the third most common malignancy and the second leading cause of death worldwide. Efficient non-invasive blood-based biomarkers for CRC early detection and prognosis are urgently needed. Methods To identify novel potential plasma biomarkers, we applied a proximity extension assay (PEA), an antibody-based proteomics strategy to quantify the abundance of plasma proteins in CRC development and cancer-associated inflammation from few μL of plasma sample. Results Among the 690 quantified proteins, levels of 202 plasma proteins were significantly changed in CRC patients compared to age-and-sex-matched healthy subjects. We identified novel protein changes involved in Th17 activity, oncogenic pathways, and cancer-related inflammation with potential implications in the CRC diagnosis. Moreover, the interferon γ (IFNG), interleukin (IL) 32, and IL17C were identified as associated with the early stages of CRC, whereas lysophosphatidic acid phosphatase type 6 (ACP6), Fms-related tyrosine kinase 4 (FLT4), and MANSC domain-containing protein 1 (MANSC1) were correlated with the late-stages of CRC. Discussion Further study to characterize the newly identified plasma protein changes from larger cohorts will facilitate the identification of potential novel diagnostic, prognostic biomarkers for CRC.